2020
DOI: 10.3389/fphys.2020.00978
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, a Multi-Ion Channel Blocker That Preferentially Blocks Late Na+ Current and Prevents I/R-Induced Arrhythmias

Abstract: Increasing evidence shows that Curcumin (Cur) has a protective effect against cardiovascular diseases. However, the role of Cur in the electrophysiology of cardiomyocytes is currently not entirely understood. Therefore, the present study was conducted to investigate the effects of Cur on the action potential and transmembrane ion currents in rabbit ventricular myocytes to explore its antiarrhythmic property. The whole-cell patch clamp was used to record the action potential and ion currents, while the multicha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Curcumin, a flavonoid found in Curcuma longa L rhizomes, has shown to have a wide range of cardioprotective effects ( 25 ). Song et al ( 26 ) evaluated the antiarrhythmic effects of curcumin (30 mM) and indicated its ability to reduce the incidence and duration of I/R-induced ventricular tachyarrhythmias (VT) and ventricular fibrillation (VF) in Langendorff-perfused rabbit hearts. In in vitro analysis, curcumin reduced the AP duration and suppressed early afterdepolarization (EAD) and Ca 2+ -induced DADs through inhibiting multiple ion channel currents, specifically late Na + channel current ( I Na–L ) and, to some extent, voltage-gated L-type Ca 2+ current ( I Ca–L ) and transient Na + current ( I Na–T ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin, a flavonoid found in Curcuma longa L rhizomes, has shown to have a wide range of cardioprotective effects ( 25 ). Song et al ( 26 ) evaluated the antiarrhythmic effects of curcumin (30 mM) and indicated its ability to reduce the incidence and duration of I/R-induced ventricular tachyarrhythmias (VT) and ventricular fibrillation (VF) in Langendorff-perfused rabbit hearts. In in vitro analysis, curcumin reduced the AP duration and suppressed early afterdepolarization (EAD) and Ca 2+ -induced DADs through inhibiting multiple ion channel currents, specifically late Na + channel current ( I Na–L ) and, to some extent, voltage-gated L-type Ca 2+ current ( I Ca–L ) and transient Na + current ( I Na–T ).…”
Section: Resultsmentioning
confidence: 99%
“…We discussed the antiarrhythmic effects of some active ingredients, including liriodenine, curcumin, cinnamophilin, and resveratrol, through inhibiting Nav channels in previous subsections. Studies have shown that these phytochemicals also behave like class III AADs, as they can modulate the K + channel currents and affect AP duration, thereby protecting the heart against I/R-induced arrhythmias ( 24 , 26 , 29 , 32 , 33 , 36 ). Note that the inhibition of Ca 2+ channels by curcumin, cinnamophilin, and resveratrol might alleviate the prolonged AP duration exerted by inhibiting K + channels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The currents of the HCN4 channel were measured utilizing the whole-cell patch-clamp approach in a manner that has been previously described [ 27 , 28 ]. BMSCs were detached using trypsin and subcultured onto glass coverslips for a minimum of 30 minutes prior to patch clamping.…”
Section: Methodsmentioning
confidence: 99%
“…Patch-Clamp Techniques. Calcium currents were recorded using whole-cell voltage-clamp techniques, as previously reported [23,24]. Currents were digitized at a sampling rate of 5 kHz.…”
Section: Simultaneous Detection Of Hipsc-cm Contraction Andmentioning
confidence: 99%